A COMPARISON OF UNDERSTANDING, BENEFIT EXPECTATION, AND BENEFIT SATISFACTION TOWARD SOCIAL SECURITY SYSTEM: A CASE OF RESIDENTS IN MUAK LEK MUNICIPAL AREA, MUAK LEK DISTRICT, SARABURI PROVINCE - Putsom, Wanlee; Mom, Rey; Saetae, Dusrudee; Sutawong, Patchara (11th International Scholars Conference, 2016)
This research aims to study the levels of understanding, benefit expectation and satisfaction toward the Social Security System and to compare these factors with different demographic profile. A total of 100 residents in Muak Lek Municipal Area, Muak Lek District, Saraburi Province, participated in this study through self- administered questionnaire. Statistics used in data analysis were frequency, percentage, mean, standard deviation, Independent t-test, and One-way ANOVA. The demographic profile analysis results showed that 65% of respondents were female, 59% were 20 to 30 years old, 58% were single, 62% worked in the private organizations, 73% have never received Social Security information, 45% of medical assistances were from the Social Security Fund, and 65% of respondents have never taken their right in Social Security System. The results showed that respondents have moderate levels of understanding, benefit expectation, and benefit satisfaction toward the Social Security System. Expectation in maternity leave allowance posed highest level (¯X = 3.86) and satisfaction in emergency allowance of 300 Baht and duration of treatment posed lowest level (¯X = 2.93). Respondents who had difference in gender, marital status, information notification, and treatment rights did not have different level in understanding, benefit expectation, and benefit satisfaction at .05 level.